Síntese de novos derivados cumarínicos-1,2,3-triazólicos - Silva, Danilo Aniceto da (2023)
In the research and development of new compounds for pest control, the use of secondary metabolites as inspiration models becomes an important alternative for the synthesis of new organic compounds. In this context, coumarins belong to a class of substances that present structural diversity and a varied number of biological activities, including fungicide. In addition, coumarins are considered a privileged scaffold due to their ability to perform interactions with various biological targets. In contrast, the 1,2,3-triazole heterocyclic compounds also have a broad spectrum of bioactivities, such as fungicide, insecticide and herbicide. Thus, the objective of this work was to synthesize new coumarin compounds, containing 1,2,3-triazole fragments. The synthesis of coumarin-1,2,3-triazole derivatives was carried out using Knoevenagel condensation reactions, esterification and cycloaddition between a terminal alkyne and an organic azide, catalyzed by copper (I). The “click” reaction (or CuAAC) between the alkyne containing the coumarin fragment and different aromatic azides was the key step of the synthetic route, as it is a stereospecific, highly efficient reaction with high yields. The sixteen coumarin-1,2,3-triazole derivatives described in this work, 3a-p, were obtained with yields ranging from 47 to 92% and their structures were elucidated by spectroscopic techniques in the infrared region and 1H, 13C and HSQC nuclear magnetic resonance. The unpublished derivatives were satisfactorily synthesized and characterized and will be forwarded to different biological assays to evaluate their fungicidal activities.